Evaluasi Pemilihan Electric Submersible Pump (ESP) Untuk Menggantikan Gas Lift (GL) Di Sumur X Lapangan Offshore Y - Nugroho Marsiyanto; Eko Prasetio; Aly Rasyid (JURNAL BHARA PETRO ENERGI, 2022)
Well X is located in the offshore Y field, where there are 7 production wells, all of which use an artificial lift in the form of a gas lift. In this field, oil is produced from the N oil layer while the gas layer comes from the K layer. Well X was drilled in May 2013 with a target of N oil formation at a depth of 9,007 ft MD, slope (450) and 4-1/2" Liner completion. The initial production of well X was 1,632 BOPD; 5.3 MMSCFD; 0% BSW. Well X is the only well in the Y offshore field that does not penetrate the K gas formation, so gas production from nearby wells is used to produce oil from the N formation. well-to-well gas lift. Along with production time, the reservoir pressure in the N oil layer and K gas layer has decreased, so that oil production in well X has also decreased. With changes in company policy that optimize and increase gas production to increase gas sales to the industry around the company's operational areas since early 2017, the outgoing pressure on the Y platform has increased from 210 psi to 450 psi, causing a total oil well X could not pass through and produce due to high outgoing pressure on platform Y. Well X's last production data was on January 31 2017 with oil production of 179 BOPD and 1.25 MMSCD for gas production and gas lift injection of 0.75 MMSCFD, before finally shutting down. The selection of another artificial lift as a substitute for the gas lift has been carried out to revive well X later. Based on the alloy table made by Weatherford for the selection of artificial lifts for conditions on the Y field platform, ESP has many advantages and appropriate flexibility compared to other types of artificial lifts. The ESP type D1050N which is a mix flow ESP has been selected and after installation in well X in August 2019 it has successfully revived with a production test of 885 BFPD, 681 BOPD, and 23% water content on September 3 2019. ESP in well X has been in production for 2 years, until finally experiencing a leaky tubing problem in September 2021 and requiring a new tubing replacement job along with a new ESP replacement to revive the X well. Reference: Brown, E., Kermit, (1977). The Technology of Artificial Lift Method”, Volume 2a, Oklahoma; Pennwell Publishing Company. Brown, E., Kermit (1980). The Technology of Artificial Lift Method”, Volume 3a, Oklahoma; Pennwell Publishing Company. Data-data Lapangan Sumur X Lapangan Offshore Y. (2019-2021). Gabor, Takack. (2009). Electric Submersible Pump Manual Desingn, Operations and Maintenance. United States of America: Gulf Publishing Company. Weatherford. (2005). Artificial Lift System.